Thermodynamic Understanding of Impurity Phase Segregation in a PdCrO2/CuCrO2 Heterostructure - Tom Ichibha; Sangmoon Yoon; Jong Mok Ok; Mina Yoon; Ho Nyung Lee; Fernando A. Reboredo (Advanced Physics Research, 2023)
Abstract PdCrO2 films are synthesized on CuCrO2 buffer layers on Al2O3 substrates. This synthesis is accompanied by impurity phase segregation, which hampers the synthesis of high quality PdCrO2 films. Potential causes ofth impurity phase segregation are studied by using a combination of experiments and ab initio calculations. X‐ray diffraction and scanning transmission electron microscopy experiments reveal impurity phases of CuxPd1 − x alloy and chromium oxides, Cr2O3 and Cr3O4, in PdCrO2. Calculations determine that oxygen deficiency can cause the impurity phase segregation. Therefore, preventing oxygen release from delafossites can suppress the impurity phase segregation. The amounts of Cr2O3 and Cr3O4 depend on temperature and oxygen partial pressure. A reasonable theory‐based explanation for this experimental observation is provided.